Non-traditional marketing methods for a survey of consumer behaviour - Kochmaruk, Maria; Vasilko, T.; Chornous, Lyudmila (My University, 2013)
The article deals with examination and analyzing some kinds of non-traditional marketing analyses which can be used in the consumer behaviour survey. Advantages and disadvantages of non-traditional marketing analyses are substantiated. Recommendations about effective application for optimal analysis which takes to account types of objects under examination were developed.
Keywords: optimal analysis; consumer behavior; neuromarketing; оптимальний аналіз; кулхантинг; поведінка споживача; нейромаркетинг; кафедра економіки праці та менеджменту